Dinamika Konseling Lintas Budaya pada Mahasiswa Melayu di Lingkungan Minangkabau - Suci Amelia; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Indonesia is a multicultural country characterized by diversity in culture, language, and social communication patterns. Cultural differences in higher education settings often create communication barriers and adjustment difficulties for students from other regions. This study aims to examine the dynamics of cross-cultural counseling for Malay students in a Minangkabau cultural environment and to understand the forms of communication barriers and social adaptation processes experienced by these students. This study employs a qualitative approach using a case study design. The research subject is a Malay student pursuing education in a Minangkabau cultural environment. Data collection techniques included observation, in-depth interviews, and documentation, while data analysis utilized the Miles and Huberman model. The results indicate that students face communication barriers due to differences in language, communication styles, and social customs, leading to feelings of awkwardness, shyness, and low self-confidence. Cross-cultural counseling helps students improve their interpersonal communication skills, understand cultural differences positively, and strengthen their social adaptation skills through empathy techniques, role-playing, and cultural psychoeducation. In conclusion, cross-cultural counseling plays a crucial role in helping students build harmonious social relationships in a multicultural environment.